INTERIOR BRANDING: ISSUES AND OPPORTUNITIES FOR INTERIOR DESIGN BUSINESSES - Andi, Pricilia Yunita; Kusumowidagdo, Astrid (Aksen : Journal of Design and Creative Industry, 2024)
The interior design industry is growing, but this is also accompanied by increased competition. To successfully stand out, companies need to differentiate themselves by emphasizing the power of interior branding. The purpose of this research is to find out the advantages of applying interior branding to the interior as a strategy in increasing the value of a company. Conducted qualitatively, the research involved observing various consultancies in Indonesia and reviewing relevant literature. Expert validation was used as triangulation. Findings highlighted industry challenges, such as adapting to client needs and market forces is the threat of recession and global crisis that can affect the Indonesian economy, including the post-pandemic shift to the commercial segment. In addition, emerging trends such as technological advancements, socio-cultural influences, and regulatory complexities pose both threats and opportunities. Utilizing interior branding presents a strategic advantage by differentiating the company through brand characteristics and meeting the demands of an emerging market. One significant trend involves the utilization of technology to increase client satisfaction when designing interiors, potentially popular interior designs in helping companies improve interior branding, and understanding regulations that protect interior design work. Ultimately, this research confirms the efficacy of interior branding as a competitive advantage in the interior design consulting business. Keywords: Competitive Advantage, Design Business, Interior Branding, Sense of Place.